SYMBOLIC INTERACTIONISM ON THE CREATIVE MESSAGE ART OF MENTAWAI TATTTOOS AS A SUBCULTURAL IDENTITY - Anita Rosana; Ahmad Sihabudin; Suraya Mansur; Irfan Fauzi (Bajang Institute, 2023)
This research focuses on the interaction of the Mentawai people of Indonesia in communicating traditional Mentawai tattoo symbols, and how the construction of the meaning of these symbols in the young Mentawai generation as an effort to preserve traditional tattoo art culture in the midst of modern culture. Most young Mentawai generation spread throughout Indonesia has assimilated with modern culture by using modified creative content of Mentawai traditional tattoo symbols as their identity. This study uses symbolic interactionism theory and use a phenomenological method with a qualitative approach and a constructivist paradigm. The data collection technique uses in-depth interviews with the people who practice Mentawai tattoo culture. In this study, there were 3 informants who still practiced traditional Mentawai tattoos and 3 informants who were modifying Mentawai tattoo into creative content. Data analysis techniques perform horizonalization, clustering the invariant constituent into themes, individual textural and structural descriptions, composites, and synthesis. The study found that there was a change in the meaning of the Mentawai tattoo symbols in the creative messages of custom tattoos. Tattoos were used as a tool to communicate ethnic identity, social recognition, and professional identitiy, then tattoos norm have changed to aesthetics, tribal pride, self-identity, and self-expression of the love of art and traditional tattoos. The younger generation continously reconstructing the creative messages and meanings of Mentawai tattoos that adapt to modern culture. Conclusion: the change in the dominant Mentawai culture into a subculture is caused by a social movement making tattoos creatively by the younger generation as the identity of the Mentawai cultural tribe from traditional to custom tattoos